Sense of Purpose in Life and Subsequent Physical, Behavioral, and Psychosocial Health: An Outcome-Wide Approach - Kim, Eric S; Chen, Ying; Nakamura, Julia S; Ryff, Carol D; VanderWeele, Tyler J (American journal of health promotion, 2022)
Growing evidence indicates that a higher sense of in life ( ) is associated with reduced risk of chronic diseases and mortality. However, epidemiological studies have not evaluated if change in is associated with subsequent health and well-being outcomes. We evaluated if positive change in (between t ; 2006/2008 and t ;2010/2012) was associated with better outcomes on 35 indicators of physical health, health behaviors, and psychosocial well-being (at t ;2014/2016). We used data from 12,998 participants in the Health and Retirement study-a prospective and nationally representative cohort of U.S. adults aged >50. We conducted multiple linear-, logistic-, and generalized linear regressions. Over the 4-year follow-up period, people with the highest (versus lowest) purpose had better subsequent physical health outcomes (e.g., 46% reduced risk of mortality (95% CI [0.44, 0.66])), health behaviors (e.g., 13% reduced risk of sleep problems (95% CI [0.77, 0.99])), and psychosocial outcomes (e.g., higher optimism (β = 0.41, 95% CI [0.35, 0.47]), 43% reduced risk of depression (95% CI [0.46, 0.69]), lower loneliness (β = -0.35, 95% CI [-0.41, -0.29])). Importantly, however, purpose was not associated with other physical health outcomes, health behaviors, and social factors. With further research, these results suggest that sense of purpose might be a valuable target for innovative policy and intervention work aimed at improving health and well-being.